2017
DOI: 10.1111/nep.12733
|View full text |Cite
|
Sign up to set email alerts
|

Less contribution of mast cells to the progression of renal fibrosis in Rat kidneys with chronic renal failure

Abstract: This study demonstrated for the first time that mast cells are neither increased nor activated in the fibrotic kidneys of CRF rats. Compared to T-lymphocytes or macrophages that proliferate in situ within the fibrotic kidneys, mast cells were less likely to contribute to the progression of renal fibrosis associated with CRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…These experiments revealed that MCs did not crucially impact the later phase of the disease and fibrosis development, as no differences became apparent between PBS-and DT-treated animals. Of note in this context, Baba et al (55) recently showed in a rat model of chronic renal failure unchanged fibrosis progression after tranilast treatment, a potent MC stabilizer. Thus, our data strongly support that the degree of initial injury by MCs represents the major factor of pathologic development, calling for early MC-targeting therapeutic interventions as suggested recently (41).…”
Section: Discussionmentioning
confidence: 96%
“…These experiments revealed that MCs did not crucially impact the later phase of the disease and fibrosis development, as no differences became apparent between PBS-and DT-treated animals. Of note in this context, Baba et al (55) recently showed in a rat model of chronic renal failure unchanged fibrosis progression after tranilast treatment, a potent MC stabilizer. Thus, our data strongly support that the degree of initial injury by MCs represents the major factor of pathologic development, calling for early MC-targeting therapeutic interventions as suggested recently (41).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Tranilast was shown to be without effect against fibrosis in rats with chronic renal failure. 244 In a study by Palaniyandi Selvaraj et al 197 , it was demonstrated that disodium cromoglycate reduced the fibrosis during autoimmune myocarditis, and this compound also reduced atrial fibrosis occurring after pressure overload in a mouse model, 199 fibrosis after implantation of biomaterials, 194 kidney fibrosis in the unilateral ureteral obstruction model 188,191 and the development of liver fibrosis in multidrug resistance two knockout mice. 245 However, since cromoglycate has been shown to have effects outside of its impact on MCs, 246 it is not certain that effects of this compound are mediated through MCs as opposed to other targets.…”
Section: Other Pharmacological Approaches To Target Mast Cells In Fmentioning
confidence: 99%
“…However, Tranilast was equally efficient in MC‐competent vs ‐deficient mice, suggesting that the impact of Tranilast was not due to effects mediated by MCs. In addition, Tranilast was shown to be without effect against fibrosis in rats with chronic renal failure . In a study by Palaniyandi Selvaraj et al, it was demonstrated that disodium cromoglycate reduced the fibrosis during autoimmune myocarditis, and this compound also reduced atrial fibrosis occurring after pressure overload in a mouse model, fibrosis after implantation of biomaterials, kidney fibrosis in the unilateral ureteral obstruction model and the development of liver fibrosis in multidrug resistance two knockout mice .…”
Section: Targeting Mast Cell Function In Fibrosismentioning
confidence: 99%
“…Renal cross sections were fixed in 4% paraformaldehyde, embedded in paraffin, and deparaffinized in xylene, and then 3 μ m sections were stained with hematoxylin-eosin (H&E) and Masson's trichrome. For fibrosis analysis, Masson's trichrome deposition, expressed as percentages of Masson's trichrome-positive areas relative to the total area, was quantified in each field and averaged, as described in our previous studies [16, 2123].…”
Section: Methodsmentioning
confidence: 99%
“…Mast cells were identified by their characteristic metachromasia. For quantitative analysis, the numbers of CD3-, ED-1-, toluidine blue-, MPO-, Ki-67-, and α -SMA-positive cells were counted in high-power fields of the cortical interstitium as described in our previous studies [16, 2123].…”
Section: Methodsmentioning
confidence: 99%